Nonnative EFL Teachers' Speaking Anxiety: Post-Communist Country Context. (April 2019) - Kralova, Zdena; Tirpakova, Anna
The current study aims to fill the gap in the current literature by focusing on the wide scale of nonnative English as a Foreign Language (EFL) teachers' perceptions and opinions in the specific context of a post-Communist country. It focuses on the link between five demographic variables (age, the length of English language study, English teaching experience, stay in English-speaking countries, and the intensity of communication with English native speakers) of Slovak EFL teachers and their English speaking anxiety (ESA) and English speaking quality (ESQ). The teachers' self-perceived causes, consequences, factors, and needs concerning their ESA were also detected. Data were collected by both qualitative methods (questionnaire and interview) and quantitative methods (scale and test). The correlation analyses revealed a negative relationship between most variables and teachers' anxiety and a positive relationship between their age and anxiety. Both qualitative and quantitative results reflect the specifics of teaching EFL in a post-Communist country.